Kebijakan Pemerintah dalam Penjaminan Mutu Pendidikan - Dewi Martalia Kurniasari (Intizam, Jurnal Manajemen Pendidikan Islam, 2021)
Quality education as a pillar of development through the development of individual potential cannot be separated from efforts to improve the quality of education. This is certainly realized by the government so that various policies appear to realize quality education. However, the situation faced by the government is in fact not only in improving quality, but also related to the equalization of education itself. The government has included regulations that have been elaborated technically and applicatively in seeking the realization of guaranteed quality education. However, quality assurance of education is not only the duty of the government, but covers all components that are in education, especially related to the education process itself. As part of the dynamics of education, we should not only rely on government policies, but also contribute to the maximum by carrying out a role in education as well as possible.